Ecophysiology of Brachiaria decumbens in grazing systems - Ramos,Letícia Moura (2018)
Plant Ecophysiology was used as a tool to interpret the responses and adaptation of pastures to environmental conditions. The objective of this study was to evaluate ecophysiological parameters in Brachiaria decumbens grown in different grazing systems in the Cerrados biome in the south state of Maranhão, Brazil. The experiment was conducted in a completely randomized design with nine replications, using a 3×2×3 factorial arrangement consisted of three grazing management systems (silvopastoral, a rotation system with regeneration of native vegetation, and extensive) two seasons (dry and rainy), and three evaluation times along the day. The photochemical efficiency, performance index, and estimation of chlorophyll content were evaluated. According to the results, most of the parameters of the variables evaluated for B. decumbens presented stress conditions, thus compromising their photosynthetic apparatus. B. decumbens presented the best photochemical efficiency and estimated chlorophyll content throughout the day in the silvopastoral system, in both evaluated seasons, therefore, it is a promising species of grass for this system.